Student Agency: an Analysis of Students’ Networked Relations Across the Informal and Formal Learning Domains - Rappa, N.; Tang, Kok-Sing (Springer, 2016)
Agency is a construct facilitating our examination of when and how young people extend their own learning across contexts. However, little is known about the role played by adolescent learners’ sense of agency. This paper reports two cases of students’ agentively employing and developing science literacy practices—one in Singapore and the other in the USA. The paper illustrates how these two adolescent learners in different ways creatively accessed, navigated and integrated in-school and out-of-school discourses to support and nurture their learning of physics. Data were gleaned from students’ work and interviews with students participating in a physics curricular programme in which they made linkages between their chosen out-of-school texts and several physics concepts learnt in school. The students’ agentive moves were identified by means of situational mapping, which involved a relational analysis of the students’ chosen artefacts and discourses across time and space. This relational analysis enabled us to address questions of student agency—how it can be effected, realised, construed and examined. It highlights possible ways to intervene in these networked relations to facilitate adolescents’ agentive moves in their learning endeavours.